Collaborative Digital Leadership in Strengthening Vocational School Quality - Fathimah Azzahro Hanifah; Endang Sri Budi Herawati (Journal of Education and Teaching Learning, 2026)
This study analyzed digital collaborative leadership in strengthening vocational-school quality at SMKN 1 Rangkasbitung. The main problem was the persistence of administrative supervision, fragmented teacher-performance data, and limited real-time visibility of classroom learning and internship activities. A qualitative case-study design was used through document analysis, digital-practice observation, and semi-structured interviews with nine purposively selected informants: the principal, vice principals, information-technology team, teachers, and students. The findings showed that ESEMKA BESTARI and TEWAK functioned not merely as administrative applications but as governance instruments for reorganizing supervision, discipline, and data-based decision making. Transformative leadership built shared urgency for measurable quality improvement; innovative leadership institutionalized digital workflows; and collaborative leadership expanded accountability by positioning teachers and students as data producers. The study concluded that digital leadership becomes effective when technology adoption is accompanied by cultural reconstruction, ethical data governance, teacher capacity building, and continuous evaluation of platform usefulness.